The Historical Dynamics of Chinese Politics - Yang, Guangbin. author. aut Link
XXV, 391 p. 18 illus., 5 illus. in color.
Keywords: This book puts forward a new perspective, the historical dynamics of Chinese politics, for better understanding China’s politics, which is from the vertical history of China and the dimension of horizontal world politics, combining the historical analysis of how Chinese politics has come along the way and the comparative analysis of China's governance achievements in world politics. Based on this premise, this book attempts to explain the democratic discourse of contemporary Chinese political logic. The historical dynamics of Chinese politics comes from long-term communication between the author and Western scholars, which may help the global audience to understand China’s politics from all angles.